Production of Ethanol from Cocoa Pod Hydrolysate - Othman Abd Samah; Salihan Sias; Yeap Geok Hua; Nurul Nadiah Hussin (Journal of Mathematical and Fundamental Sciences, 2011)
Cocoa pod (Theobroma cacao L.) hydrolysate was hydrolyzed into glucose using hydrochloric, sulphuric and nitric acids, respectively. The concentration of each acid was set at 0.25 M, 0.50 M, 0.75 M, 1.00 M and 1.25 M. They were treated under two different temperatures and time at 75¢ªC and 90¢ªC for 2 h and 4 h, respectively. The results showed that hydrolysis in 1.00 M of hydrochloric acid at 75¢ªC for 4 h had produced the highest glucose content of 30.7% w/v compared to all others acids treated under similar conditions. The pod¡¯s hydolysate was then fermented in batch culture using Saccharomyces cerevisiae for 48 h at 30¢ªC. A maximum ethanol production of 17.3%v/v was achieved after 26 h of fermentation time.